Impact of Emerging International Order on Security in Middle East - D. S. Krylov (Контуры глобальных трансформаций: политика, экономика, право, 2023)
The modern system of international relations is currently in a stage of dynamic transformation. The changes that are taking place in it affect not only the global level, but also the interaction between states at the regional level. In the article the influence of the world order on the processes in the field of security, which is one of the many areas of cooperation and confrontation between the center powers, both regional and global, is being analyzed. The analysis has shown a high level of conflict potential in the Middle East region, long-term and versatile contradictions among the key cross-regional powers (Egypt, Israel, Iran, Turkey and Saudi Arabia), as well as the need to build a security system in the region that could later be integrated into the world architecture. As a result, it is concluded that the inclusive security architecture being formed by Russia in the Middle East, taking into account the preservation of opportunities for equal dialogue of interested parties, could become an effective structure for maintaining peace and stability at the regional level, as well as the basis for a new world order, in the context of the global security architecture, in which the center powers of the world scale will be involved.